Control de temperatura de un sistema de ventilación forzada para el sector de Latacunga - Tipán Guanochanga, Jhonny Patricio (2022)
The current technological project describes "Temperature control of a forced ventilation system for Latacunga sector" where different control methods for heat reduction are analyzed that starting with the temperature data taken in the laboratory of simulation, electrical and electromechanical tests, with the Extech HT30 brand thermal stress meter, then the corresponding calculations are made for the selection of the control elements where the primary elements selected are the Pt100 temperature sensor together with LOGO 12 /24 RCE, so we proceed to the connection of the control and implementation panel. Based on this fact, a manual is developed which explains the operation of each element implemented in the project, which will allow the user to know the operation of the control panel and thus avoid suffering an electrical accident during handling. Finally, the system is integrated with the combination of the forced ventilation system and temperature control, complying with regulations and technical standards to achieve its purpose.